Microbial resources : from functional existence in nature to applications - Kurtboke, Ipek (Academic Press, 2017)
'Microbial Resources: From Functional Existence in Nature to Applications' provides an exciting interdisciplinary journey through the rapidly developing field of microbial resources, including relationships to aspects of microbiology. Covers the functional existence of microorganisms in nature, as well as the transfer of this knowledge for industrial and other applications. Examines the economic perspective of revealing the potential value of microbial material and figuring it into socio-economic value; legal perspectives; and how to organize a fair allotment of socio-economic benefits to all stakeholders who have effectively contributed to the preservation, study, and exploitation of microbiological material. Key Features: Covers aspects of foundational information related to microbiology, microbial ecology, and diversity, as well as new advances in microbial genomics; Provides information on the utilization of microbial resources in biotechnology; Covers legislative issues and related law in biodiscovery; Fills a need for a very broad audience and is a good resource for microbiologists seeking to know the extent of microbiology approaches, the policies associated with microbiology, and potential career paths for researchers; Has significant added value due to the inclusion of comprehensive coverage of the biology, ecology, biochemistry and international legislation surrounding these applications. --